Grass, barley, grass and maize silages produced with or without selenium enriched fertilizers and offered to Belgian Blue suckling cows: a 3 years survey - Cabaraux, J.F; Paeffgen, S; Hornick, J.L; Schoonheere, N; Istasse, L; Dufrasne, I (MTT, 2005)
In Belgium, the selenium (Se) content in locally produced feedstuffs is low. Since October 2002, the Belgian Blue herd of the Experimental Station was divided in two groups (control and Se groups). Fertilizers enriched or not with Se were spread on pastures used for grazing or for the production of grass silage and on fields in which winter barley or maize were grown. The use of Se enriched fertilizer increased the Se content in grass of grazed pastures by 4.8 times (248.3 vs. 51.8µg/kg DM), in grass silage by 3.5 times (186.9 vs. 53.4µg/kg DM), in winter barley by 6.5 times (286.3 vs. 43.7µg/kg DM) and in maize silage by 3.8 times (27.0 vs. 102.4µg/kg DM). The blood Se content measured by the activity of glutathione peroxidase remained low at 27.2µg/l in the cows of the control group. By contrast the blood Se content started to increase on the end of the first winter period in the Se group. During the first grazing period, the concentration sharply increased to reach a plateau at 80µg/l. The concentration decreased then during the winter period at an average concentration of about 55µg/l. The pattern of Se concentration was similar during the following two seasons. These lower concentrations during the winter period were associated to the relative contribution of Se enriched feedstuffs in the winter diet. It appeared thus from the present trial that Belgian Blue cows responded to a large extent to a Se supplementation by feedstuffs grown with Se enriched fertilizers.
Keywords: Ka; Belgian Blue herd; selenium fertilization; glutathione peroxidase